Effects of coagulation medium on asymmetric polyethersulfone membrane for carbon dioxide and methane separation - MUTUN, JESSICO (2010)
This study is concentrated on the ability and the performance of the asymmetric polyethersulfone membrane in gas separation process. Asymmetric flat sheet membranes were prepared by using a simple dry/wet phase inversion method. Experimental investigations were conducted focusing on the effect of the different coagulation medium during the phase inversion toward the permeability and the selectivity of the membrane to the carbon dioxide and methane gases. Three different coagulants medium were used which were water, methanol and water/methanol (50:50). The flats sheet asymmetric membrane then being characterized by using the scanning electron microscopy (SEM) and the Fourier transform infrared spectroscopic (FTIR). Gas permeation tests then run to examine the effect of the different coagulants toward the time of the gases pass through the membrane. From the result of the gas permeability unit calculation, membrane which immersed in water solution has shown the highest permeability. Different coagulant medium will affect the performance of the membrane toward its permeability and selectivity of gases. The water medium solution is the best coagulation medium for the asymmetric polyethersulfone membrane during the phase inversion method with the GPU value of 3.23. As for the conclusion, water is identified as the best coagulation medium for asymmetric polyethersulfone membrane.